2021
DOI: 10.18502/jovr.v16i4.9749
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Head Optical Coherence Tomography Angiography Findings after Coronavirus Disease

Abstract: Purpose: To quantify the microvasculature density of the optic nerve head (ONH) using optical coherence tomography angiography (OCTA) analysis in patients recovered from Coronavirus Disease 2019 (COVID-19). Methods: In a comparative cross-sectional, observational study, patients recovered from COVID- 19 whose initial diagnosis was confirmed by an rRT-PCR of a nasopharyngeal sample were included in this study. OCTA of ONH was performed in included patients and normal controls. Vascular density (VD) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…A decrease in vessel density (VD) in the superficial and deep capillary plexus, as well as an increase in inner disk small vessel VD which can be associated with optic disk hyperemia and edema, has been documented. [5][6][7] These alterations suggest that COVID-19 infection puts patients at risk of choroidal and optic nerve disorders. mentioned, in our patient, bilateral painless vision loss occurred first, and pain was added after four days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in vessel density (VD) in the superficial and deep capillary plexus, as well as an increase in inner disk small vessel VD which can be associated with optic disk hyperemia and edema, has been documented. [5][6][7] These alterations suggest that COVID-19 infection puts patients at risk of choroidal and optic nerve disorders. mentioned, in our patient, bilateral painless vision loss occurred first, and pain was added after four days.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the retinal and optic nerve head microvasculature have been identified in previous research. A decrease in vessel density (VD) in the superficial and deep capillary plexus, as well as an increase in inner disk small vessel VD which can be associated with optic disk hyperemia and edema, has been documented 5–7 . These alterations suggest that COVID‐19 infection puts patients at risk of choroidal and optic nerve disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Virgo and Mohamed [15] reported two patients with par central acute middle maculopathy (PAMM) and acute macular neuroretinopathy following SARS-CoV-2 infection which can be incidental. Insausti-Garcı´a et al [16] reported a case of papillophlebitis associated with COVID19. Most of these cases of Retinal vasculitis or Retinal Ischemia in literature were either a case report or small sample studies.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the retinal and optic nerve head microvasculature have been identified in previous research. A decrease in vessel density (VD) in the superficial and deep capillary plexus, as well as an increase in inner disc small vessel VD which can be associated with optic disc hyperemia and edema, have been documented [6][7][8] . These alterations suggest that COVID-19 infection puts patients at risk for retinal and optic nerve disorders.…”
Section: Discussionmentioning
confidence: 99%